Administration values in the mainland Chinese and Hong Kong public services: a comparative analysis - Scott, Ian; Gong, Ting (2014)
Public bureaucracies shape the values of their officials in ways that affect performance and behaviour. By contrasting those administrative values in mainland China and Hong Kong and how they impact on such issues as attitudes towards the organisation, superior-subordinate relationships, conflict and conflict avoidance and responsiveness to change, the character of the bureaucracy and the dynamics of interactions within it can be better understood. From the findings, the most important determinant of differences is that the prevailing conception on the mainland is of a bureaucracy where authority is lodged in the person ("rule of man"), whereas in Hong Kong, Weberian bureaucracy ("rule of law") is the dominant form. The study draws both on quantitative material derived from the same survey conducted among senior civil servants on the mainland and in Hong Kong and on qualitative material from interviews with officials. - Reproduced.
Keywords: Administrative law; Rule of law; Civil service